REGIONAL APPROACH TO THE DEVELOPMENT OF A TOURIST PRODUCT - KOSHKALDA, Iryna; KALINICHENKO, Sergiy; GROKHOLSKYI, Vadim; GRIBINYK, Andrey (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Tourism through the formation of destinations opens up great opportunities for socio-economic development of territories (countries, regions, cities, etc.) with different amounts of tourist resources. Inbound tourism helps to increase the country's balance of payments, domestic - its preservation. Tourism allows you to make a profit in many industries, industries and fields of activity that are involved in the formation of tourism or tourism-related products. Tourism should be developed in any country, region, the main thing - to have a correct idea of its specifics and information support when planning relevant activities related to it. The regions of Ukraine have a significant and diverse tourist and recreational potential, due to the favorable geopolitical position and natural and climatic conditions, which may be in demand in both domestic and international tourism markets. However, recent crises related to the quarantine crisis, which has caused negative socio-economic processes around the world, are significant challenges to the development and realization of regional potential of tourism business in Ukraine - the need for effective regional mechanisms to stimulate development of all components of tourism which should be a prerequisite for realizing the potential of the region's tourism industry. The regional approach to research and development of tourism allows analyze in detail sociocultural and socio-economic aspects of tourism business development, to promote effective use of tourist and recreational potential of regions, formation of post-industrial stage of economic system and regions.
Keywords: tourist sphere tourist product; tourist industry; region; tourist and recreational resources